Focusing on the communication with the patient: An introductory course at the Medical School of the University of Crete - Λιονής (Christos Lionis) Χρήστος (Bioethica, 2018)
This brief report focuses on the communication between doctor-patient and provides the brief description of the skills that should accompany the doctor in his / her meeting with the patient. This review article refers also to the experience gained at the Medical School of Crete where a course on the "doctor-patient relationship" and on “compassionate health care” have been included in its medical curriculum.